Teachers and Practitioners. - Carey, John L. (The Accounting Review, 1969)
Abstract The article discusses the importance of good communications and cooperation between the academic and practicing branches of the accounting profession. Over the years it has become increasingly apparent that good communications and cooperation between the academic and practicing branches of the accounting profession are vitally important to the continued satisfactory development of the accounting profession. Over the years the atmosphere has continued to change for the better. Cooperation between teachers and practitioners has extended over a wide front both on an individual and an institutional basis. The accounting profession is going through an unusual and difficult period. As in other areas of our society, basic assumptions are being challenged. The adverse publicity-whether well founded or not which was directed at the profession several years ago created a good deal of uneasiness both within and without the profession. Relations between teachers and practitioners have vastly improved in the past thirty years. But they can improve more. There could be more frequent personal association between teachers and practitioners at the local level-although in some states this already is happening.